Development and Validation of the Commuting Safety Management Coordinator Module - Md Isa, Mohd Hafzi; Bakar, Harun; Wan Mohamed, Wan Mazlina; Khelf, Mouloud (Environment-Behaviour Proceedings Journal, 2025)
The lack of commuting safety management at workplaces is a contributing factor to the increase in commuting accidents in Malaysia. Thus, this study aimed to develop and validate a Commuting Safety Management Coordinator module using the Design and Development Research (DDR) approach integrated with the Sidek Module Development Model (SMDM). The module, consisting of 11 units, was reviewed by 11 experts through a Focus Group Discussion (FGD) and achieved a content validity level of 87%, indicating strong content validity. The validated module supports organizations in enhancing commuting safety practices and warrants further research on module reliability and effectiveness.